2021
DOI: 10.3390/molecules26144124
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Profiling of Ipsilateral Brain and Plasma after Celastrol Post-Treatment in Transient Middle Cerebral Artery Occlusion Mice Model

Abstract: Celastrol, a pentacyclic triterpene isolated from the traditional Chinese medicine Tripterygium wilfordii Hook. F., exhibits effectiveness in protection against multiple central nervous system (CNS) diseases such as cerebral ischemia, but its influence on lipidomics still remains unclear. Therefore, in the present study, the efficacy and potential mechanism of celastrol against cerebral ischemia/reperfusion (I/R) injury were investigated based on lipidomics. Middle cerebral artery occlusion (MCAO) followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In another study, researchers analyzed the profiles of LncRNAs and mRNAs following celastrol treatment of MCAO by RNA-sequencing and bioinformatic analysis and experimentally verified the significantly different LncRNAs and mRNAs ( Liu J. et al, 2022 ). Liu et al used ultra-performance liquid chromatography-tandem mass spectrometry (UPLC/MS) to perform lipidomic analysis after celastrol treatment of MCAO and obtained some differentially expressed components ( Liu M. et al, 2021 ). These studies have provided a theoretical basis for subsequent in-depth investigations.…”
Section: Effects Of Triptolide and Celastrol On Brain And Spinal Cord...mentioning
confidence: 99%
“…In another study, researchers analyzed the profiles of LncRNAs and mRNAs following celastrol treatment of MCAO by RNA-sequencing and bioinformatic analysis and experimentally verified the significantly different LncRNAs and mRNAs ( Liu J. et al, 2022 ). Liu et al used ultra-performance liquid chromatography-tandem mass spectrometry (UPLC/MS) to perform lipidomic analysis after celastrol treatment of MCAO and obtained some differentially expressed components ( Liu M. et al, 2021 ). These studies have provided a theoretical basis for subsequent in-depth investigations.…”
Section: Effects Of Triptolide and Celastrol On Brain And Spinal Cord...mentioning
confidence: 99%
“…What’s interesting, the KEGG pathway analysis also suggested that lipid metabolism may play a potential role in neuroprotection of celastrol. More recently, a study found lipid metabolism partially regulated the neuroprotection of celastrol on cerebral I/R injury through the lipidomic analysis ( Liu M. et al, 2021 ), but the underlying mechanism need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The brain slices were scanned and the infarct size was analyzed using Image J software (National Institutes of Health, Bethesda, MD, United States) by researchers who were blinded to the study group. In order to exclude the effect of cerebral edema, the following calculation formula was used: (contralateral hemisphere area–ipsilateral non-ischemic hemisphere area)/contralateral hemisphere area × 100% ( Liu M. et al, 2021 ). Five male mice were used in each group.…”
Section: Methodsmentioning
confidence: 99%
“…In our recent study, we presented evidence that celastrol directly bound to HMGB1 to inactivate it, up-regulated HSP70 and down-regulated NF-κB expression to play a neuroprotective effect in cerebral ischemia-reperfusion (I/R) injury in vitro and in vivo [ 27 ]. Lipidomics and enrichment analysis after MCAO model in mice showed that celastrol exhibited neuroprotection and anti-apoptosis effects partially by modulating lipid metabolites in sphingolipid and glycerophospholipid metabolism pathways [ 70 ]. Celastrol significant attenuated I/R-induced hippocampal injury by inhibiting the AK005401/MAP3K12 signaling and activating the PI3K/Akt pathway [ 71 ].…”
Section: Neuroprotective Effects Of Celastrol In Neurodegenerative Di...mentioning
confidence: 99%